The effect of electric turbulent flow pressure in the intake system on diesel engine emissions and performance - D.A. Muntaha; A. Sanata; M.F.R. Hentihu; N. Ilminnafik; S.N.H. Syuhri (Universitas Mataram, 2026)
Current diesel engine technology development is directed at improving performance and fuel efficiency in line with the demands of exhaust emission control. One potential approach to achieve this goal is intake system engineering through airflow conditioning. This study aims to experimentally investigate the effect of applying pressure electric turbulent flow (PETF) to the intake system on the characteristics of the intake airflow, engine performance, fuel consumption, and exhaust emissions of a standard 2300 cc diesel engine. Testing was conducted by comparing engine conditions without PETF and with PETF at several engine speed levels under steady-state operating conditions. The parameters described include intake air pressure and temperature, torque, effective power, Brake Specific Fuel Consumption (BSFC), and soot opacity as an indicator of particulate emissions. The results show that the application of PETF increases intake air pressure and improves intake flow characteristics, which results in increased torque and effective power, especially at low to medium speeds. In addition, the use of PETF results in a decrease in BSFC and soot opacity values compared to the condition without the device, indicating increased combustion efficiency and reduced particulate formation. Overall, these results indicate that pressure electric turbulent flow has the potential to be an applicable approach to improve the performance, fuel efficiency, and emission control of standard production diesel engines without requiring internal engine modifications.